Methodology for the Accounting Recognition of Negative Environmental Externalities in the Cafeterium Sector Companies of the State of Veracruz - Sinforoso-Martínez, Saulo; Ricardez-Jiménez, Jerónimo Domingo; Salazar-Arrieta, Fernando (Journal of Environmental Accounting and Management, 2026)
Negative environmental externalities are the impacts caused by organizations to natural resources that lack economic value in the market, such as water, air, etc., authors such as Gray (1992), Tua (1995), Larrinaga (1997), Prugh et al. (1999), Llull (2001), Salas (2015) among others, affirm that they must be incorporated into the cost of the product as a means for sustainable development. Given the interest of the coffee companies of the state of Veracruz to integrate them into their cost of production, a methodology is proposed. The study is carried out applying the Life Cycle of a Product, the Election Experiment Method and Process Costing. The result is that Veracruz coffee companies will be able to identify and classify their negative environmental externalities through the Product Life Cycle, the Election Experiment Method allows them to allocate an economic value and cost per process with the incorporation of a fourth element called "Sustainable Cost" will contribute to its registration and presentation. It is concluded that most of the research has focused on the identification, classification and description of negative environmental externalities and not on methodologies that allow its registration and presentation in the cost of production, which justifies the importance of this study, since for the Veracruz coffee companies have information on externalities that facilitates environmental decisionmaking.